A descriptive approach to computerised English historical corpora in the 21st century - Vázquez, Nila; Esteban Segura, Laura; Marqués Aguado, Teresa (International Journal of English Studies, 2011)
Historical corpora offer many potentialities for linguistic research. Thus, the present article provides an overview of the major English historical corpora compiled or being compiled both in Spain and abroad. They include different types such as tagged and parsed corpora, and their main features will be outlined. As for the organisation of the article, after the introductory section, the historical corpora created abroad will be presented. Then, those being constructed in Spain (Coruña, Las Palmas, Málaga, Salamanca, Santiago and Sevilla) will be discussed. Some final remarks and the references close the article.